POTENTIAL STRATEGIES AND COURSES OF ACTION FOR ENCOURANGING ROMANIAN ECO CLOTHING PRODUCERS – CHALLENGES AND TRENDS - Doina I. POPESCU (Challenges of the Knowledge Society, 2025)
The purpose of the paper is to present possible strategies and courses of action that can be adopted to encourage Romanian clothing companies towards the production of ecological clothing. The objectives of the research in the paper are to present the directions for increasing the role of sustainable industrial sectors, to identify new consumption trends in the new socio-economic context, to analyse the stage of adoption of socially responsible production methods within the Romanian clothing industry and to identify strategies that can be adopted by Romanian clothing companies in accordance with new consumption trends. The clothing industry is an innovative industrial branch both for Romania and for the member states of the European Union, concentrating the largest number of SMEs in the European industry. Within the paper the concepts of corporate social marketing, fast-fashion, slow-fashion, eco-design are also presented. The research identifies growth possibilities in the number of local producers manufacturing ecological products, by proposing the creation of integrated companies and, also, the advantages of their creation are presented. The paper is structured into the following sections: Introduction; Challenges and trends for marketing management in the new socio-economic context with the following sub-sections: Social responsibility reflected in fashion; The Romanian clothing industry and social responsibility, and Potential strategies and courses of action for encouraging Romanian eco clothing producers, Conclusions and References.